2018
DOI: 10.3389/fpls.2018.00196
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Vegetation Dynamics in a Megadiverse Hotspot: The Ice-Age Record of a Pre-montane Forest of Central Ecuador

Abstract: Tropical ecosystems play a key role in many aspects of Earth system dynamics currently of global concern, including carbon sequestration and biodiversity. To accurately understand complex tropical systems it is necessary to parameterise key ecological aspects, such as rates of change (RoC), species turnover, dynamism, resilience, or stability. To obtain a long-term (>50 years) perspective on these ecological aspects we must turn to the fossil record. However, compared to temperate zones, collecting continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The relatively steep slopes and lack of marshy vegetation surrounding both lakes would have increased the probability that charcoal resulting from fires, if any, within the watershed would have been deposited into the lakes. Because sediment cores from the wet regions of the Andes and Amazonia often contain charcoal (Loughlin et al 2018;Montoya et al 2018), we do not think taphonomic processes affected our results.…”
Section: Human-free Ecological Dynamicsmentioning
confidence: 83%
“…The relatively steep slopes and lack of marshy vegetation surrounding both lakes would have increased the probability that charcoal resulting from fires, if any, within the watershed would have been deposited into the lakes. Because sediment cores from the wet regions of the Andes and Amazonia often contain charcoal (Loughlin et al 2018;Montoya et al 2018), we do not think taphonomic processes affected our results.…”
Section: Human-free Ecological Dynamicsmentioning
confidence: 83%
“…The raw radiocarbon dates were calibrated using IntCal13.14c and SHCal.13.14c for L. Baños and L. Pindo respectively (Hogg et al 2013;Reimer et al 2013). The results were used to construct age-depth models in R using the statistical package 'clam.R' (Blaauw 2010), that have been published elsewhere (Matthews-Bird et al 2017;Montoya et al 2018), and are included in the Supplementary material (Figs. S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
“…Regions like the southern and southeastern Amazon have shifted between forest and open savanna vegetation in relatively recent periods of colder and drier LGM climate (Absy and Hammen 1976), whereas the Andean flank in the western (van der Hammen and Absy 1994) and eastern portions of the Amazon (Wang et al 2017) seem to have persisted as forest. Long-term ecological data from pollen analysis have shown the prevalence of various types of rainforests, both in the southwestern cloud forests and northwestern pre-montane forests of the Amazonian highlands, showing the importance of cloud cover in buffering forests when facing climate change (Urrego et al 2010;Montoya et al 2018). The presence of forests with distinct composition during the LGM has also been observed in the northwestern Brazilian Amazon (Bush et al 2004;D'Apolito et al 2013).…”
Section: Past Evidence Of the Dynamics Of Amazonian Ecosystems Since ...mentioning
confidence: 98%
“…When a forest is disturbed, the rates of ecosystem change observed in sedimentary archives depend on the ecological scale, being abrupt (decadal) at the species level, but gradual (centennial) at the community level (Montoya et al 2018(Montoya et al , 2019. In a tropical meta-data analysis of forest recovery rates after disturbances based on pollen records, Cole et al (2014) observed that South American forests required an average of 325 years to recover from disturbances (natural and human-induced).…”
Section: Past Evidence Of the Dynamics Of Amazonian Ecosystems Since ...mentioning
confidence: 99%